Learning through personal connections: cogenerative dialogues in synchronous virtual spaces. Issue 3 (2nd April 2016) - Bondi, Stephanie; Daher, Tareq; Holland, Amy; Smith, Adam R.; Dam, Stacy
ABSTRACT: This study describes the role of cogenerative dialogues in a synchronous virtual classroom. Cogenerative dialogues are a way for students and instructors to reflect upon in-class events and work collaboratively during the course to optimize teaching and learning. In the present study, cogen has been found to be a tool for enhancing connections among graduate students in the class leading to a reported increase of motivation and engagement. Cogenerative dialogues were essential in shifting responsibilities so that students took a more active role in their own learning while supporting each other.